Ventriculoperitoneal shunt malfunction diagnosis based on substance dilution. Issue 31 (6th August 2021) - Fu, Xinjie; Chen, Yuhang; Duan, Weike; Yang, Haixin; Xu, Jiulin; Cheng, Xiaobing; Zhang, Hongri
Abstract: Objective: Current methods for the diagnosis of ventriculoperitoneal (VP) shunt malfunction lack specific standards; therefore, it may be missed or misdiagnosed. Hence, providing a reliable diagnostic method will help improve the accuracy of preoperative decision-making. Therefore, the aim of the study was to provide a new method for the diagnosis of VP shunt malfunction. Methods: After in vitro testing, we enrolled a total of 12 patients with VP shunt malfunction. Before revision surgery, 0.1 mL of a 5% sodium valproate (SV) solution was injected into the reservoir; 0.1 mL of the cerebrospinal fluid (CSF) was withdrawn 20 minutes later from the reservoir to measure the SV concentration. The process was repeated on the seventh day after surgery and compared with the preoperative results. Results: The mean ± standard deviation preoperative SV concentration in the cerebrospinal fluid was greater than the postoperative concentration (5967.8 ± 1281.3 vs 391.1 ± 184.6 μg/mL, P = .001). Conclusion: The proposed method is a reliable, safe, and relatively simple alternative for the diagnosis of VP shunt malfunction and further provides a reference for treatment.